Paradiplomacy in Creating Regional Competitiveness: Case Study of Jember Regency - Fathun, Laode Muhamad (Indonesian Perspective, 2021)
This paper describes the paradiplomacy of the Jember Regency. This paper shows that the Jember Regency’s paradiplomacy through city diplomacy can act as an actor who can cooperate with countries such as Japan and Canada in various fields in order to be a safe and comfortable regency. In doing so, the local government seeks to create international connections through sister cities and smart cities. This effort is a strategy to enter the digital era, which demands more innovative and creative regions. Jember Regency uses a conservative type of paradiplomacy which in line with the Ministry of Foreign Affairs as the foreign relations coordinator. Thus, the relationship built is in the form of a joint coordinator formula and parallel harmony between the capital city and the local government. In addition, educational cooperation was conducted by the University of Jember as a form of soft power to introduce many foreigners’ artistic identity, values, and local culture.